Pesantren and the Political Authority of Kiai: The Dialectic of Religion, Power, and Education - Zainuddin Zainuddin; Ani Nafisah; Mustafiyanti Mustafiyanti; Davik Davik (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
This study examines the political engagement of Kiai in the development of pesantren in South Sumatra amid political decentralization and increasing competition among educational institutions. The involvement of Kiai in local politics is understood as an adaptive strategy to access public resources and strengthen the institutional capacity of pesantren. Although the political roles of Kiai have been widely discussed, empirical studies that specifically examine their impact on the structure, quality, and governance of pesantren education remain limited. This study aims to analyze how the political practices of Kiai influence institutional legitimacy, curriculum development, and the competitiveness of pesantren. Using a qualitative phenomenological approach guided by patron–client theory, data were collected from three major pesantren in South Sumatra through in-depth interviews, participant observation, and document analysis. The findings indicate that ethical and proportionate political engagement by Kiai can accelerate infrastructure development, diversify educational programs, and enhance institutional recognition. However, excessive dependence on political networks poses risks to pesantren institutional autonomy and may erode the moral authority of Kiai as religious leaders. This study underscores the importance of maintaining a balance between religious leadership and political engagement to ensure that pesantren remain credible and sustainable centers of Islamic education.